A weak lensing estimate from GEMS of the virial to stellar mass ratio in massive galaxies to z~0.8 - Heymans, C; Bell, E; Rix, H; Barden, M; Borch, A; Caldwell, J; McIntosh, D; Meisenheimer, K; Peng, C; Wolf, C; Beckwith, S; Haeussler, B; et al. (2006)
We present constraints on the evolution of the virial to stellar mass ratio of galaxies with high stellar masses in the redshift range 0.2<z<0.8, a="" by="" combo-17.="" comparing="" complete="" estimates="" for="" from="" galaxies="" lensing="" log(m_star="" m_\odot)="" m_star="" m_vir="" mass="" measurements="" of="" sample="" stellar="" to="" virial="" weak="" with=""> 10.5, where the majority show an early-type morphology, we find that the virial mass to stellar mass ratio is given by M_vir/M_star = 53^{+13}_{-16}. Assuming a baryon fraction from the concordance cosmology, this corresponds to a stellar fraction of baryons in massive galaxies of Omega_b^*/\Omega_b = 0.10 +/- 0.03. Analysing the galaxy sample in different redshift slices, we find little or no evolution in the virial to stellar mass ratio, and place an upper limit of ~2.5 on the growth of massive galaxies through the conversion of gas into stars from z=0.8 to the present day.</z<0.8,>